2020
DOI: 10.1158/1557-3265.covid-19-po-030
|View full text |Cite
|
Sign up to set email alerts
|

Abstract PO-030: Outcome of older cancer patients infected with Covid19 at Gustave Roussy Cancer Center

Abstract: Background: The SARS-CoV-2 outbreak in Paris’s region significantly affected Gustave Roussy Cancer Center. Previous analyses showed that mortality rate increases with age in the general population. Here, we report the Gustave Roussy experience on older patients (OP) with cancer during the SARS-CoV-2 outbreak. Methods: Cancer pts with suspected SARS-CoV-2 infection were admitted at Gustave Roussy starting March 12th. Screening indications have been adapted over the time. All the COVID19 pts posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In this study from France, 137 cancer patients were diagnosed with COVID-19, with 36 patients (26%) 70 years or older [8]. They found that age was not associated with clinical worsening (hazard ratio: 1.157; 95% CI: 0.55-2.42; p = 0.07).…”
Section: Outcomes Of Older Cancer Patients Infected With Covid-19 At Gustave Roussy Cancer Centermentioning
confidence: 85%
“…In this study from France, 137 cancer patients were diagnosed with COVID-19, with 36 patients (26%) 70 years or older [8]. They found that age was not associated with clinical worsening (hazard ratio: 1.157; 95% CI: 0.55-2.42; p = 0.07).…”
Section: Outcomes Of Older Cancer Patients Infected With Covid-19 At Gustave Roussy Cancer Centermentioning
confidence: 85%